Experimental Study on Cu/Oil Nanofluids through Concentric Annular Tube: A Correlation. Issue 3 (12th January 2016) - Jafarimoghaddam, Amin; Aberoumand, Sadegh; Aberoumand, Hossein; Javaherdeh, Kourosh
Abstract : This study deals with an empirical investigation on the convective heat transfer of Cu/oil nanofluid flow inside a concentric annular tube with constant heat flux boundary condition and suggests a correlation to predict the Nusselt number. The average size of particles was 20 nm and the applied nanofluid was prepared by Electrical Explosion of Wire technique with no nanoparticle agglomeration during nanofluid preparation process and experiments. The nanofluid flowing between the tubes is heated by an electrical heating coil wrapped around it. The effects of different parameters such as the flow Reynolds number, tube diameter ratio, and nanofluid particle concentration on heat transfer coefficient are studied. Using the acquired experimental data, a correlation is developed for the estimation of the Nusselt number of nanofluid flow inside the annular tube. This correlation has been presented by using the exponential regression analysis and least‐squares method. The correlation is valid for Cu/base oil nanofluid flow with weight concentrations of 0.12, 0.36, and 0.72 in the hydrodynamically full‐developed laminar flow regime with Re <140, which is applicable in mini‐ and microchannel heat exchangers, and it is in good agreement with the experimental data.